2022
DOI: 10.54393/pbmj.v5i3.339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stretching Exercise and Tens Therapy on Severity of Restless Legs Syndrome in Obese Population

Abstract: Restless legs syndrome (RLS) is a disorder in which you have an uncontrolled need to move your legs, generally in response to an unpleasant feeling. It usually happens in the evening or at night, while you're seated or lying down. Moving briefly alleviates the uncomfortable sensation. Objective: To determine effects of stretching exercises and TENS therapy on severity of restless leg syndrome in obese population. Materials and Methods: In this single-blinded, randomized, controlled study, 30 subjects with RLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies in patients with RLS on hemodialysis have indicated that 4‐to 6‐month aerobic exercise and stretching exercises lowered the severity of symptoms compared with control or dopamine treatment 27–32 . Although there are studies on the effectiveness of aerobic exercise and stretching exercises in patients with primary RLS, there is no comparison between the exercises 33,34 . Exercise has been shown to modulate dopamine and glutamate neurotransmission and synaptogenesis and enhance regional cerebral blood flow 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in patients with RLS on hemodialysis have indicated that 4‐to 6‐month aerobic exercise and stretching exercises lowered the severity of symptoms compared with control or dopamine treatment 27–32 . Although there are studies on the effectiveness of aerobic exercise and stretching exercises in patients with primary RLS, there is no comparison between the exercises 33,34 . Exercise has been shown to modulate dopamine and glutamate neurotransmission and synaptogenesis and enhance regional cerebral blood flow 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 studies investigating exercise with potentially primary RLS can be compared with our study in terms of sample size. Esteves et al included only 11 participants, 4 and the Haider et al study included 30 patients with RLS who were obese with no exclusion criteria for anemia or pregnancy 34 . In the study by Aukerman and colleagues, which is a pioneering study in terms of exercise in patients with RSL, secondary conditions were excluded, and the study was completed with only 28 patients 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation